An effect of dynamic logistics capabilities on courier’s business performance - Noneng Nurjanah; Agus Rahayu; Lili Adi Wibowo; Nanang Fattah (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
Courier companies face environmental challenges influenced by the development of e-commerce businesses, demanding high service quality and reliability in meeting consumer demand. Courier companies demand toimmediately adjust company strategies to be able to survive in competitive market conditions, the only way is to continue to keep dynamic on internal capability. This study develops and tests a model of the relationship between dynamic logistic capabilities, environmental turbulence, and business performance. As quantitative research, a survey was used to collect data. A sample of 70 valid answers from courier company members of the Association of Indonesian Express Delivery, Postal, and Logistics Services Companies(ASPERINDO) was treated through the Partial Least Square (PLS) method. The research results show a full mediation relationship between dynamic logistics capability and business performance, given the proportion of the impact of dynamic logistics capabilities on business performance (72.7%) identified in this study. As a result, the main result points out that the positive correlation between dynamic logistics capabilities and business performance strengthens the relationship evidence in the literature that dynamic logistics capabilities contribute to business performance, that is, sales growth, delivery reliability and security.